1986
DOI: 10.1111/j.1365-2222.1986.tb01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies against native, processed and digested cow's milk proteins in children with cow's milk protein intolerance

Abstract: Summary Children with or without cow's milk protein intolerance were investigated for serum antibodies to native cow's milk proteins, processed cow's milk proteins and native‐ and pepsin‐digested β‐lactoglobulin. Antibodies of IgG and IgA isotypes were determined with ELISA and those of IgE isotype with RAST. Children who exhibited slowly appearing untoward reactions to cow's milk feeding had significantly higher titres of IgG antibodies against both native and digested β‐lactoglobulin than children with an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…The antigenicity (Fallstrom et al 1986;Gortler and Urbanek 1990;Leary, Jr. 1992;Wahn et al 1992) and immunogenicity (Stephan et al 1990;Cordle et al 1991) of protein hydrolysates and milk proteins (Wahn et al 1981) have recently been studied in animal and human models. These studies demonstrated a decreasing antigenicity with the increasing degree of hydrolysis due to the reduction of epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenicity (Fallstrom et al 1986;Gortler and Urbanek 1990;Leary, Jr. 1992;Wahn et al 1992) and immunogenicity (Stephan et al 1990;Cordle et al 1991) of protein hydrolysates and milk proteins (Wahn et al 1981) have recently been studied in animal and human models. These studies demonstrated a decreasing antigenicity with the increasing degree of hydrolysis due to the reduction of epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…IgE antibodies, which were evident in sera from most patients with allergy to hen's egg white but not from healthy subjects, play a major role in food hypersensitivity reactions, especially immediate type (type I) of allergic re action within the intestinal tract [24], In contrast, IgG and IgA antibodies to foods have been found in both foodallergic subjects [13,14] and healthy children [25]. Evi dence for involvement of IgG and IgA classes of immu noglobulin in food sensitivity reactions is much less con vincing.…”
Section: Discussionmentioning
confidence: 99%
“…The IgE, IgG and IgA class antibodies for OVA have been shown to exist in sera from patients with allergy [13,14]. RAST inhibition test demonstrated that allergenic epitopes are mainly determined by primary structure and OVA peptides 1-10 and 323-339 encompass allergenic epi topes, which are recognized by IgE antibodies from pa tients with allergy to hen's egg white [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This is probably a physiological phenomenon, as most exposed individuals have low levels of antibodies in serum against cow's milk proteins, including b -lactoglobulin, as well as cereal proteins such as gliadin [2][3][4].…”
Section: Introductionmentioning
confidence: 99%